Computational analysis of the effect of bogie inclination angle on landing gear noise - Mierlo, K. J. van; Takeda, K.; Peers, E.; Takeda, Kenji (Proceedings of the 16th AIAA/CEAS Aeroacoustics Conference. 16th AIAA/CEAS Aeroacoustics Conference, 2010)
Airframe noise and in particular main landing gear noise is a major noise source during the approach phase. Wind tunnel tests have shown a strong relationship between the inclination angle of the bogie and the noise radiation of a main landing gear. Using Computational Fluid Dynamics, this paper investigates the flow features around three different configurations of a simplified four wheel main landing gear. The three configurations consist of a horizontal, 10 degree toe up and 10 degree toe down bogie inclination angle. The unsteady CFD results have been used as an input to a FW-H solver to determine far field noise levels. The results show that strong vortices are generated when the flow separates from the front wheels. The interaction of these vortices with the solid landing gear surface is the main mechanism of noise generation. The results from the simulations show a clear relationship between the bogie inclination angle, the location of the strong vortex cores and the far field noise levels.